Pengaruh Flexible Working Time Dan Motivasi Kerja Terhadap Kinerja Pegawai Badan Pangan Nasional - Regan Bintang Lazuardi; Murniyati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Abstract - In the modern era, work time flexibility and motivation have become crucial factors in improving employee performance. Flexible Working Time is considered a solution to achieving work-life balance, while work motivation remains a key driver of productivity. This study aims to examine the influence of Flexible Working Time and Work Motivation on Employee Performance, both partially and simultaneously. A quantitative method with multiple linear regression analysis was used. Data were collected through questionnaires distributed to employees. The results show that Flexible Working Time has a significant negative effect on performance, with a regression coefficient of -0.283 (p < 0.05), while Work Motivation has a significant positive effect with a coefficient of 0.266 (p < 0.05). Simultaneously, both variables significantly affect employee performance, with an F-value of 7.875 and an R² of 0.651. This indicates that 65.1% of the variation in performance can be explained by the model, while the remaining 34.9% is influenced by other factors.